2016
DOI: 10.1093/gerona/glv225
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Back Pain and Risk of Falls Among Older Community-dwelling Women

Abstract: Older community-dwelling women with a recent history of back pain are at increased risk for falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 62 publications
7
43
3
3
Order By: Relevance
“…Two recent systematic reviews and meta‐analyses have demonstrated a link between pain and falls, and prospective studies included in the reviews provided evidence that pain is associated with an increased risk of falls in the older population . This has been further supported by recent findings from prospective studies . In addition, the associations appear to be more pronounced with an increasing number of painful sites .…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Two recent systematic reviews and meta‐analyses have demonstrated a link between pain and falls, and prospective studies included in the reviews provided evidence that pain is associated with an increased risk of falls in the older population . This has been further supported by recent findings from prospective studies . In addition, the associations appear to be more pronounced with an increasing number of painful sites .…”
Section: Introductionmentioning
confidence: 64%
“…MSP has been shown to be associated with multiple health outcomes, including physical and psychological domains and is being recommended as a geriatric syndrome . A link between pain and risk of falls has been documented in prior as well as recent studies. Further, risk for falls was more pronounced with increasing number of painful sites .…”
Section: Discussionmentioning
confidence: 97%
“…Given that poor balance control is a risk factor for falls in the geriatric population, [30] our findings of increased step width during gait may begin to explain why other studies have consistently demonstrated that older adults with CLBP are at increased risk for falling as compared to pain-free elders. [3133] These findings of greater step width in the CLBP population may indicate that more thorough assessment and treatment of balance is required in the geriatric CLBP population.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Blyth et al () performed with a community sample, it was determined that the incidence of falls was higher among older adults who reported pain, similar to the results of our study. Similarly, in the studies by Patel et al (), Stubbs et al (), Mitchell et al (), and Marshall et al (), it was revealed that pain that was severe and on various sites was associated with falls. Only a weak correlation was found between falls and pain in a number of other studies (Bekibele & Gureje, ; Lazkani et al, ; Leveille et al, ; Muraki et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…Despite the presence of several plausible mechanisms for the contribution of pain in falls, few studies have investigated the relationship between pain and falls among older adults (Bekibele & Gureje, ; Blyth, Cumming, Mitchell, & Wang, ; Leveille et al, ; Muraki et al, ; Patel et al, ; Stubbs et al, ). If pain is a risk factor for falls, this represents a potentially important point of intervention for falls prevention (Marshall et al, ; Mitchell et al, ).…”
Section: Introductionmentioning
confidence: 99%